Delhi Airport Metro Express Private Limited - Raghuram, G., 1955- ([London] : SAGE, 2016)
Delhi Metro Airport Express Line (AEL) from New Delhi Metro Station to Dwarka Sector 21 linked the Indira Gandhi International Airport. The line was operated by the Delhi Airport Metro Express Pvt Limited (DAMEPL), a subsidiary of Reliance Infrastructure (RInfra), the concessionaire of the line. However, DAMEPL has been unable to run the AEL profitably ever since it started operations due to poor ridership and high operating costs. After three months in October 2012, with the repairs nearly completed, RInfra had to take a call on the way forward. This case outlines the options available.
Originally Published in: Raghuram, G. (2014). Delhi Airport Metro Express Private Limited. CIPR0017. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Railroads -- Management -- Case studies; Project management -- Case studies